The cognitive effects of different feedback modalities in virtual reality learning. In S. L. Wong et al. (Eds.), Proceedings of the 18th International Conference on Computers in Education, Putrajaya, Malaysia: Asia-Pacific Society for Computers in Education. - Tan, Sze Cha; Chen, Chwen Jen (2010)
Feedback is an important feature of a virtual reality (VR) learning system as appropriate feedback increases learners’ motivation as well as interaction. This study aims to investigate the cognitive effects of using VR-based learning systems with different feedback modalities. It employs a pretest-posttest quasi-experimental design to measure the cognitive effects of VR learning systems that use on-screen text, narration, as well as both on-screen text and narration, respectively and an additional non-VR environment, which uses paper-based reference material, to serve as a control of the study. The study reveals that the differences in feedback modality, focusing on narration and on-screen text, do not significantly affect cognitive gain in a VR learning system. In addition, the significant positive effects of the VR-based learning system when compared with the non-VR method, provides another evidence of the potentials of VR technology for instructional use. This paper discusses the findings based on existing learning theories and principles, and concludes with a design implication of VR learning systems that incorporate feedback.